1997
DOI: 10.1016/s0009-2509(97)00189-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel model predicting the residence-time distribution during reactive extrusion

Abstract: A novel model predicting the residence-time distribution during reactive extrusion de Graaf, R.A.; Rohde, M.; Janssen, L.P.B.M. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim. Abstract-A new model for the residence-time distribution in a counter rotating twin-screw extruder is compared with experimental results obtained during the gelatinisation of starch and the grafting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 12 publications
(5 reference statements)
0
13
0
Order By: Relevance
“…In the literature, a constant density is often used and the shear viscosity is modeled by an empirical equation [56][57][58] or a rheological law [35,[52][53][54][55].…”
Section: Reactors-in-series Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, a constant density is often used and the shear viscosity is modeled by an empirical equation [56][57][58] or a rheological law [35,[52][53][54][55].…”
Section: Reactors-in-series Approachmentioning
confidence: 99%
“…In [56,57], the filling ratio, monomer concentration, temperatures and RTD are determined for a counter-rotating twin screw extruder using a subdivision of the screws in C-chambers (see Figure 10) where mass and energy balances are expressed using continuum mechanics. If the system includes a high inter-meshing area between the screws, other volume elements may be added to model the specific flows in this zone (see [52]).…”
Section: • Models With Predetermined Screw Discretizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Equal residence time can be achieved if the volume divided by the throughput remains constant, or, if we define Z as the average residence time [4,8]:…”
Section: Similarity In Residence Timesmentioning
confidence: 99%
“…They showed that back pressure exists only in the presence of die component at the end of an extruder. Graaf et al (1997) derived the mathematical model that describes the residence time distribution of reactive and non-reactive system of starch extrusion in a counter rotating twin-screw extruder. The model based on the polymer moments successfully predicted the sensitivity of parameters such as screw speed, filling length of screw and throughput, on the process.…”
Section: Introductionmentioning
confidence: 99%